VARIAÇÃO DE PALAVRAS-CHAVE ENTRE GÊNEROS DE UM CORPUS JORNALÍSTICO - Kauffmann, Carlos H. (Intercâmbio, 2010)
This study examines from a Corpus Linguistics perspective (Berber Sardinha, 2004) main keywords occurring across daily press genres in Brazilian Portuguese. The keywords observed, e.g. verbal lemmas and personal pronouns, may indicate recurrent presence and/or absence in different selected genres.